2022
DOI: 10.1111/trf.17084
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life after restrictive versus liberal RBC transfusion for cardiac surgery: Sub‐study from a randomized clinical trial

Abstract: Background Transfusion Requirements in Cardiac Surgery III (TRICS III), a multi‐center randomized controlled trial, demonstrated clinical non‐inferiority for restrictive versus liberal RBC transfusion for patients undergoing cardiac surgery. However, it is uncertain if transfusion strategy affects long‐term health‐related quality of life (HRQOL). Study Design and Methods In this planned sub‐study of Australian patients in TRICS III, we sought to determine the non‐inferiority of restrictive versus liberal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…For example, one study found worse QoL outcomes at 12, 18, and 24 months in participants exposed to a restrictive as compared to a liberal transfusion strategy. However, we believe it is unlikely that transfusion administered many months before would impact QoL so many months later 32 . Measuring functional outcomes within days to few weeks seems more likely to relate to a specific transfusion strategy rather than longer time periods.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, one study found worse QoL outcomes at 12, 18, and 24 months in participants exposed to a restrictive as compared to a liberal transfusion strategy. However, we believe it is unlikely that transfusion administered many months before would impact QoL so many months later 32 . Measuring functional outcomes within days to few weeks seems more likely to relate to a specific transfusion strategy rather than longer time periods.…”
Section: Discussionmentioning
confidence: 92%
“… 10–30 Three additional RCTs reporting outcomes of fatigue or other QoL measures were identified in the updated search (Table 1). 31,32 Two trials were excluded because the scores for each arm were not available in a format that could be used for analysis, 33,34 and one trial was excluded for evaluating immediate versus delayed transfusion 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Level of disability and quality of life are important outcomes when considering patients with chronic diseases. Postoperative functional recovery has also become a rising concern and focus 14,15 . Recently, dedicated scales, including the 12‐item WHODAS 2.0 (World Health Organization Disability Assessment Schedule 2.0) and the QoR‐15 (Quality of Recovery, 15 items), have been used to document patient‐centered outcomes in recent randomized controlled trials and observational studies in perioperative setting 2,16–19 …”
Section: Introductionmentioning
confidence: 99%
“…Postoperative functional recovery has also become a rising concern and focus. 14,15 Recently, dedicated scales, including the 12-item WHODAS 2.0 (World Health Organization Disability Assessment Schedule 2.0) and the QoR-15 (Quality of Recovery, 15 items), have been used to document patient-centered outcomes in recent randomized controlled trials and observational studies in perioperative setting. 2,[16][17][18][19] Pilot studies to test feasibility and acceptability are essential to validate the design of large randomized trials.…”
Section: Introductionmentioning
confidence: 99%